Risk assessment of mould growth on spruce wood during transport in an intermodal container - Kržišnik, Davor; Lesar, Boštjan; Thaler, Nejc; Grbec, Samo; Humar, Miha (Maderas. Ciencia y Tecnología, 2018)
Microclimatic conditions (relative humidity and temperature) were monitored in a shipment of Norway spruce (Picea abies) wood inside an intermodal container on its 66-day transport from Slovenia to Japan. In parallel, the susceptibility of Norway spruce wood to moulding fungi was determined and a dynamic vapour sorption analysis was performed. Considerable moulding developed on specimens that were exposed to a climate with relative humidity above 93%. The results of the laboratory assessment correlated with the observations of mould development in the container. The relative humidity in the container was below 93%, so there was no mould growth on the transported Norway spruce wood.